(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
In this paper, performance of voltage source inverter.(VSI) fed Permanent Magnet Brushless DC Motor(PMBLDCM) with Power Factor Correction (PFC) is discussed. A power factor correction converter is suggested at the input to correct the power factor on the input side. The conventional circuit is improved by introducing double boost converter at the input side. The Pulse Width Modulation (PWM) inverter fed Permanent Magnet Brushless DC motor system with L-filter, T-filter and double boost converter are simulated and the results are presented. The performance of PMBLDCM operating with the above mentioned converters is studied. By digital simulation, the characteristics of the PMBLDCM system are investigated. FFT analysis for various converters is presented. The simulation results indicate improved performance. Key words : VSI; Double boost converter; PMBLDC; Harmonic reduction; PWM; PFC; Sim power systems DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9591 BJSIR 2011; 46(4): 457-464